2015
DOI: 10.1093/glycob/cwv014
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan sulfation determines the biochemical properties of prion protein aggregates

Abstract: Prion diseases are transmissible neurodegenerative disorders associated with the conversion of the cellular prion protein, PrP(C), to a misfolded isoform called PrP(Sc). Although PrP(Sc) is a necessary component of the infectious prion, additional factors, or cofactors, have been shown to contribute to the efficient formation of transmissible PrP(Sc). Glycosaminoglycans (GAGs) are attractive cofactor candidates as they can be found associated with PrP(Sc) deposits, have been shown to enhance PrP misfolding in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…Of interest, it has been demonstrated that Aβ-oligomers and DNA-aptamers drive the liquid-solid phase transition of rPrP through the interaction of amino acid residues around 90 to 120 (58,59). Furthermore, both full-length prion protein and prion protein peptide (amino acid, 23-144) could form proteinase-resistant, spherical-ellipsoid aggregates that grow as amyloid fibrils by the addition of detergent or polysaccharides, thus supporting our hypothesis that liquid-solid phase transition is associated with prion diseases (60)(61)(62). However, given that several reports have successfully demonstrated the acquisition of seeding activity from rPrP/PrP C by adding RNA, lipid, and other proteins (63)(64)(65), our results argue that the acquisition of PK resistance of rPrP from LLPS alone is not sufficient for seeding activity.…”
Section: Discussionsupporting
confidence: 76%
“…Of interest, it has been demonstrated that Aβ-oligomers and DNA-aptamers drive the liquid-solid phase transition of rPrP through the interaction of amino acid residues around 90 to 120 (58,59). Furthermore, both full-length prion protein and prion protein peptide (amino acid, 23-144) could form proteinase-resistant, spherical-ellipsoid aggregates that grow as amyloid fibrils by the addition of detergent or polysaccharides, thus supporting our hypothesis that liquid-solid phase transition is associated with prion diseases (60)(61)(62). However, given that several reports have successfully demonstrated the acquisition of seeding activity from rPrP/PrP C by adding RNA, lipid, and other proteins (63)(64)(65), our results argue that the acquisition of PK resistance of rPrP from LLPS alone is not sufficient for seeding activity.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, other works have noted the induction of stable, spherical, non-toxic PrP aggregates by heparin, and found that partially 2-O-, 3-Odesulfated heparin has reduced ability to form fully protease resistant, thioflavin T reactive PrP Sc [55].…”
Section: Aggregating Proteins In the Nervous Systemmentioning
confidence: 71%
“…Furthermore, our results showed that the abilities of CSA, CSB, and CSC to stimulate Bac-PrP Sc conversion differed according to prion strains; therefore, this strain-dependent difference in CS ability to promote PrP C conversion to PrP Sc might represent one of the underlying causes of strain-specific differences in neuropathology. The binding of HP and HS has been reported to increase the thermal stability, ␤-sheet structure, or PK resistance of recPrP (12,47,48) and alter the solubility of recPrP (38); these findings suggest that PrP C binding to HS and HP induces a conformational change in PrP C . Therefore, Bac-PrP binding to HP and HS might also induce a conformational change in Bac-PrP and contribute to the conversion of Bac-PrP into Bac-PrP Sc .…”
Section: Inoculummentioning
confidence: 96%
“…Sulfate Groups on HP Are Critical for Bac-PrP res Amplification-GAG length and degree of sulfation were previously reported to affect the conversion of PrP C or recPrP into PrP Sc (9,10,(35)(36)(37)(38). Therefore, to examine the relative effects of GAG length and sulfation degree on Bac-PrP conversion into Bac-PrP res , we added chemically modified HPs to iPMCA reaction mixtures under nucleic acid-depleted conditions (Fig.…”
Section: Gags Did Not Affect Bac-prp Conversion Into a Pk-resistant Fmentioning
confidence: 99%